The association between diabetic autonomic neuropathy with thiamine deficiency - Samekto Wibowo, Samekto Wibowo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: Autonomic neuropathy is a kind of diabetes mellitus complication. Parasympathetic neuropathy occurs first, and then it is followed by sympathetic neuropathy. Autonomic nerves are widely distributed in many organs and systems, including cardiovascular, gastrointestinal, urogenital, thermoregulation, and ocular organs. Therefore, the involvement of those organs will produce certain clinical symptoms related to the functions of the internal organs. On the other hand, thiamine status influences the condition of nerve fibers. Thiamine deficiency may produce nerve impairment.Objective: To discover the association between diabetic autonomic neuropathy with thiamine deficiency. Methods: Diabetes mellitus cases of Sardjito Central General Hospital were involved in this study. Schellong test was used to diagnose autonomic neuropathy. Thiamine status was measured in The Nutrition and Food Laboratory of Gadjah Mada University by determining transketolase enzyme activity as done by Ismadi. Results: One hundred and forty subjects were involved in this study. Eleven subjects (7.9%) suffered from autonomic neuropathy. Thiamine deficiency occured in 60% of autonomic neuropathy subjects. Among the subjects without autonomic neuropathy, 55.6% suffered from thiamine deficiency. The difference was not significant (p> 0.05). Odds Ratio 1,2; 95%Cl 0.32-4,46.Conclusions: Thiamine deficiency was more prominent among diabetic autonomic neuropathy subjects. Nevertheless, diabetic autonomic neuropathy had no significant association (p > 0.05) OR 1.2; 95% CI 0.32-4.46) with thiamine deficiency.Key words: diabetes mellitus - thiamine deficiency - autonomic neuropathy - diabetic autonomic neuropathy - postural hypotension